Anatomical Variation on Some Wood Collected from Meru Betiri National Park - Serafinah Indriyani (Natural B, Journal of Health and Environmental Sciences, 2014)
Some plants that have wood economically value are found at Meru Betiri National Park, such as nyampuh (Litsea monopetala (Roxb.) Pers.), bayur (Pterospermum javanicum Jungh.), gempol kethek (Lophopetalum javanicum (Zoll.) Turcz.), suren (Toona sureni Merr.), sapen (Pomentia tomentosa T. & B.), manting (Eugenia cymosa Lamk.), pluncing (Spondias pinnata (L.F.) Kurz.), mahoni (Swietenia macrophylla King), and bungur (Lagerstoemia speciosa Pers.).  Anatomically, wood has specific and unique structure. Wood is a secondary xylem that consist of tracheary elements such as vessel and tracheid, fibers such as fiber-tracheid and libriform fiber, and parenchyma cells (ray system). The pattern of wood section is affected by intrinsic factors. Wood was sectioned in 2X1 cm² in measurement and then it was boiled during 1 hour, after that it was immersed in mixed solution glycerin and absolute alcohol (1:1) during several weeks until the wood smooth adequately to sliced. Wood was sliced by sliding microtome 20-25 µm in thickness, and then it was placed on the objectglass that contain glycerin and covered by coverglass, after that it was observed by microscope. There was anatomically variation of wood samples that observed, involved trachea and tracheid width, also schlerenchyme fiber length. Vessel of nyampuh is the biggest in diameter (35±4.7 µm), and parenchyma ray of suren is the longest in length (70±9.3 µm) among other species.